The neutrophil-lymphocyte ratio predicts all-cause and cardiovascular mortality among U.S. adults with rheumatoid arthritis: results from NHANES 1999-2020 - Zhou, Erye; Wu, Jian; Zhou, Xin; Yin, Yufeng (Frontiers in Immunology, 2023)
Background: The neutrophil-to-lymphocyte ratio (NLR) is recognized as a biomarker for systemic inflammation and immune activation. However, its connection with the mortality risk in individuals with rheumatoid arthritis (RA) is not well understood. This study aimed to investigate the association between NLR and all-cause and cardiovascular mortality risk in U.S. adults with RA. Methods: Data were gathered from the National Health and Nutrition Examination Survey (NHANES) cycles spanning 1999 to March 2020. We included adults aged ≥20 years. The NLR was computed by dividing the neutrophil count by the lymphocyte count from complete blood counts. The maximally selected rank statistics method helped identify the optimal NLR cutoff value associated with significant survival outcomes. Multivariable logistic regression models were performed to investigate the relationship between the NLR and the all-cause and cardiovascular mortality of RA. Restricted cubic spline (RCS) analyses were utilized to detect whether there were linear or non-linear relationships between NLR and mortality. Results: In this study, 2002 adults with RA were included, with 339 having a higher NLR (≥3.28) and 1663 having a lower NLR (<3.28). During a median follow-up of 84 months, 79 RA individuals died. Participants with higher NLR had a 2-fold increased risk of all-cause (HR = 2.02, 95% CI: 1.53-2.66) and cardiovascular mortality (HR = 2.48, 95% CI: 1.34-4.57) versus lower NLR, after adjusting for demographics, socioeconomic status, and lifestyle factors. Kaplan-Meier analysis revealed that the survival rate for the higher NLR group was significantly lower than the lower NLR group, in terms of both all-cause and cardiovascular mortality (both P<0.0001). The RCS curve demonstrated a positive linear association between the NLR and all-cause and cardiovascular mortality. Conclusion: A higher NLR was independently predictive of elevated long-term mortality risk in U.S. adults with RA. The NLR may serve as an inexpensive, widely available prognostic marker in RA.